2016
DOI: 10.1007/s12519-016-0026-x
|View full text |Cite
|
Sign up to set email alerts
|

Newborns’ sleep-wake cycle development on amplitude integrated electroencephalography

Abstract: The SWC on aEEG of 32-46 weeks infants showed a continuous, dynamic and developmental progress. The appearance of SWC and the narrowing bandwidth of narrowband is the main indicator to identify the CA-dependent SWC from the preterm to the late preterm period. The lower edge of the broadband identifies the term to post-term period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Amplitude‐integrated electroencephalography (aEEG) is a safe and generally well‐accepted neurophysiologic monitoring applied in preterm and term infants in neonatal intensive care units (NICUs), and the increasing numbers of newborns with associated risks of neurological disorders and the availability of new therapeutic strategies – such as trials of neuroprotection with hypothermia and antiepileptic drugs – suggest a growing need for aEEG. The interpretation of an aEEG tracing includes three categories – the classification of the background pattern, the identification of sleep–wake cycling (SWC), and the identification of seizures – all of which depend upon the infant's gestational age and different pathophysiological conditions . Previous studies reported that continuous extremely low voltage, flat tracing, or burst suppression of aEEG background patterns is correlated with unfavorable neurological outcomes in asphyxiated neonates, and recurrent seizures and status epilepticus have been shown to be indicators of poor neurodevelopmental outcomes, while fully developed SWC has been shown to be a good prognostic indicator .…”
Section: Introductionmentioning
confidence: 99%
“…Amplitude‐integrated electroencephalography (aEEG) is a safe and generally well‐accepted neurophysiologic monitoring applied in preterm and term infants in neonatal intensive care units (NICUs), and the increasing numbers of newborns with associated risks of neurological disorders and the availability of new therapeutic strategies – such as trials of neuroprotection with hypothermia and antiepileptic drugs – suggest a growing need for aEEG. The interpretation of an aEEG tracing includes three categories – the classification of the background pattern, the identification of sleep–wake cycling (SWC), and the identification of seizures – all of which depend upon the infant's gestational age and different pathophysiological conditions . Previous studies reported that continuous extremely low voltage, flat tracing, or burst suppression of aEEG background patterns is correlated with unfavorable neurological outcomes in asphyxiated neonates, and recurrent seizures and status epilepticus have been shown to be indicators of poor neurodevelopmental outcomes, while fully developed SWC has been shown to be a good prognostic indicator .…”
Section: Introductionmentioning
confidence: 99%
“…The aEEG scoring system described by Burdjalov et al [18] indicates progressive cerebral maturity, and the amount of continuous activity positively correlates with increasing postmenstrual age [21,22]. The establishment of sleep-wake cycles indicates a fundamental development of the central nervous system from immature to mature [23]. The failure to develop sleepwake cycles in preterm infants correlates with the severity of brain lesions [21,24], and in term infants suffering from hypoxic-ischemic encephalopathy, the presence of sleep-wake cycles after birth even predicts good neurodevelopmental outcome until early childhood [25].…”
Section: Discussionmentioning
confidence: 99%
“…Continuous long-term EEG monitoring is a feasible method to monitor SWC in intensive care units, particularly when using amplitude integrated EEG (aEEG) (78,(160)(161)(162)(163). SWC patterns in aEEG trends can be recognized from just a single EEG channel when clearly expressed in a term age infant.…”
Section: Techniques To Detect and Classify Infant Sleep Statesmentioning
confidence: 99%